2014
DOI: 10.1038/gt.2014.115
|View full text |Cite
|
Sign up to set email alerts
|

Antibody neutralization poses a barrier to intravitreal adeno-associated viral vector gene delivery to non-human primates

Abstract: Gene delivery vectors based on adeno-associated viruses (AAV) have exhibited promise in both preclinical disease models and human clinical trials for numerous disease targets, including the retinal degenerative disorders Leber's congenital amaurosis and choroideremia. One general challenge for AAV is that pre-existing immunity, as well as subsequent development of immunity following vector administration, can severely inhibit systemic AAV vector gene delivery. However, the role of neutralizing antibodies (NABs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(123 citation statements)
references
References 71 publications
7
115
0
1
Order By: Relevance
“…6) (Fig. 5B) is also 341 consistent with another report of cross-reactivity to AAV2 following injections of other serotypes 342 (Kotterman et al, 2015). A new contribution of our study is the finding that small vector doses 343 injected into the monkey CNS can produce high NAb titers.…”
Section: Injections Of Aav Vectors Into the Brain Made As Part Of Opsupporting
confidence: 83%
“…6) (Fig. 5B) is also 341 consistent with another report of cross-reactivity to AAV2 following injections of other serotypes 342 (Kotterman et al, 2015). A new contribution of our study is the finding that small vector doses 343 injected into the monkey CNS can produce high NAb titers.…”
Section: Injections Of Aav Vectors Into the Brain Made As Part Of Opsupporting
confidence: 83%
“…We and others have shown transduction of macaque cones using AAV variants with ubiquitous promoters (16,(29)(30)(31)(32), but achieving cone transduction by vitreally administered AAV has only been possible at high doses, leading to inflammation (16,29). We reasoned that foveal cone targeting could be achieved if we use a strong cone-specific promoter at lower intravitreally injected AAV doses compatible with safety (29,33). To test if such "dose sparing" is possible, we injected 2 macaque eyes with AAV2-7m8-PR1.7-GFP and 2 other macaque eyes were injected with AAV2-7m8-GFP under the control of the cytomegalovirus (CMV) promoter at a dose of 1 × 10 11 viral genomes (vg) per eye (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…One shortcoming with the intravitreal injection route is the higher susceptibility of AAVs administered into this compartment to interactions with the immune system compared with subretinal administration (33). It has been shown that antibody neutralization poses a barrier to intravitreal AAV vector-mediated gene delivery in NHPs, and this will likely pose a challenge for human application.…”
Section: Discussionmentioning
confidence: 99%
“…Ten NHP were chosen based on the absence of neutralizing antibody titers against AAV2 in their blood sera. 37 One primate was injected intravitreally with two vector doses (one eye with 1 Â 10 11 and the other with 5 Â 10 11 vg), with CatCh expressed under the SNCG in fusion with GFP to monitor gene expression in vivo (NHP1). As GFP can be immunogenic, 24 we used CatCh without a fluorescent tag for the remaining nine primates.…”
Section: In Vivo Inflammatory Responses In Nhp Eyesmentioning
confidence: 99%